2022
DOI: 10.1039/d1fo03908c
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of polysaccharides extracted fromPinus massonianapollen in colorectal cancer-in vitroandin vivostudies

Abstract: The prevalence and mortality rate of colorectal cancer (CRC) have been dramatically rising worldwide. Pinus massoniana pollen, a well-known natural nutrition food, is one of the most commonly consumed traditional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The homogeneity and molecular weight were measured with an Agilent 1260 Infinity size exclusion chromatography and gel permeation chromatography system equipped with an Agilent RID-7115A refractive index detector (Agilent Technologies, Palo Alto, CA, USA) and a gel-filtration chromatography column (TSK-gel G3000PWXL column, 7.8 × 300 mm i.d., 7 μm; Tosoh Bioscience LLC, Tokyo, Japan). Dextran standards (1,5,12, 50, 80 and 270 kDa) were used for calibration. Elution was performed with 0.02 M ammonium acetate solution at a rate of 0.6 mL min −1 and maintained at 35 ± 1 °C.…”
Section: Structural Characterization Of Gp90mentioning
confidence: 99%
See 1 more Smart Citation
“…The homogeneity and molecular weight were measured with an Agilent 1260 Infinity size exclusion chromatography and gel permeation chromatography system equipped with an Agilent RID-7115A refractive index detector (Agilent Technologies, Palo Alto, CA, USA) and a gel-filtration chromatography column (TSK-gel G3000PWXL column, 7.8 × 300 mm i.d., 7 μm; Tosoh Bioscience LLC, Tokyo, Japan). Dextran standards (1,5,12, 50, 80 and 270 kDa) were used for calibration. Elution was performed with 0.02 M ammonium acetate solution at a rate of 0.6 mL min −1 and maintained at 35 ± 1 °C.…”
Section: Structural Characterization Of Gp90mentioning
confidence: 99%
“…11 Studies have also shown that Pinus massoniana pollen polysaccharide treated colon cells exhibit electron-lucent cytoplasm and nuclei as well as cytoplasmic vacuolization, which are characteristic of apoptosis caused by ferroptosis. 12 The question remains whether the auxiliary antitumor activity of GPs is related to the induction of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA extraction and quantitative real-time polymerase chain reaction (qPCR) were performed as previously described. 11,12 The expression of each target gene messenger RNA (mRNA) in liver and jejunum tissues was detected by qPCR. TRIzol reagent (no.…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…Polysaccharides act against tumor cells directly or indirectly. Their direct antitumor effects are reflected in their ability to induce apoptosis in cancer cells, block the cell cycle, and inhibit tumor cell invasion, adhesion, metastasis, and growth (Shi et al, 2013;Shang et al, 2022). Secondly, the indirect antitumor effects of polysaccharides involve enhancing immune function (Feng et al, 2019).…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Vitamin A and Vitamin B12 Influencing the composition of the intestinal flora. Shao et al, 2021;Shang et al, 2022 Dietary patterns Mediterranean diet ω-3 polyunsaturated fatty acids, phytochemicals inhibit the expression of colonic inflammatory factors. Shi et al, 2013;Si et al, 2021 Vegetarian diet Reducing the intake of red meat and animal protein, adequate dietary fiber, etc., which can increase the microbial diversity of the intestine.…”
Section: Shadnoush Et Al 2013mentioning
confidence: 99%